THE EFFECT OF STUDENT FACILITATOR AND EXPLAINING (SFAE) COOPERATIVE LEARNING MODEL ON PHYSICS STUDENT’S ACHIEVEMENT - Nadia Rahmani Zulkarnain Putri; Silvi Yulia Sari; Hidayati Hidayati; Wahyuni Satria Dewi (Universitas Negeri Padang, 2023)
Low students' physics learning outcomes are an important and major problem in achieving competency. The purpose of this research was to find out whether there was a significant effect of the Student Facilitator And Explaining (SFAE) cooperative learning model on the physics learning outcomes of class XI students of Senior High School. The type of research conducted was Quasi Experimental Research with the Post-test Only Control Group Design research design. In this study, the population was all class XI Mathematics and Natural Sains students at Senior High School who were enrolled in the 2022/2023 academic year. The sample of this study was class XI Mathematics and Natural Sains 1 which was the experimental class and class XI Mathematics and Natural Sains 2 which was the control class. The research instrument consisted of a posttest and an attitude assessment sheet. The data analyzed in this study used descriptive analysis and a two-way similarity test at a significant level of 0.05 for student competencies consisting of knowledge competencies and that is, there is a significant effect of applying the Cooperative learning model of the Student Facilitator And Explaining (SFAE) type. ) on the physics learning outcomes of class XI students of Senior High School. This is supported by the results of data analysis on each of the knowledge and attitude competencies. With the two average similarity tests, the value of t count > t table was obtained, for knowledge competencies 2.05 > 2.00, and for attitude competencies 3.08 > 2.00.